Nano-Biomedical Engineering 2009 : Proceedings of the Tohoku University Global Centre of Excellence Programme Global Nano-Biomedical Engineering Education and Research Network Centre : Sendai International Centre, Sendai, Japan, 27-28 March 2009 - Yamaguchi, T. (Takami), 1948- (Imperial College Press ; Distributed by World Scientific Pub. Co., 2009)
This proceedings volume details both current and future research and development initiatives in nano-biomedical engineering, arguably the most important technology of the world in the 21st century. It deals with the following four groups of nano-biomedical engineering: nano-biomechanics, nano-bioimaging, nano-biodevices, and nano-biointervention. Consisting of a compilation of studies conducted by group members of the Tohoku University Global Center of Excellence Program, with specially coordinated funding from the Japanese Government, the papers emphasize the integration of research and education collaboration between engineering and medicine, and showcase Japan's top-level research in the field of nano-biomedical engineering.